2020
DOI: 10.1080/23802359.2020.1726228
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the complete chloroplast genome of an endangered ornamental and medicinal plant Lilium pumilum

Abstract: Lilium pumilum DC. is a useful plant species not only for its showy flowers but also for its edible and medicinal values. Here we report on the complete chloroplast genome sequence of L. pumilum. The chloroplast genome is 152,573 bp in size and includes two inverted repeat regions of 52,984 bp, which is separated by a large single-copy region of 82,009 bp and a small single copy region of 17,580 bp. A total of 130 genes were predicted, including 38 tRNA, 8 rRNA, and 84 protein-coding genes. Phylogenetic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Lilium pumilum ( L. pumilum ) is not only valuable for having the beautiful bright red ornamental flowers, but also for its strong resistance to disease, cold, drought and salinity, which makes it an unparalleled plant material in Saline-Alkali stress research [ 3 , 4 , 5 ]. Lilium pumilum in this study grows naturally in the heavily salinized and alkalized meadow of Daqing suburb of the Songnen Plain with soil pH as high as 9–10.…”
Section: Introductionmentioning
confidence: 99%
“…Lilium pumilum ( L. pumilum ) is not only valuable for having the beautiful bright red ornamental flowers, but also for its strong resistance to disease, cold, drought and salinity, which makes it an unparalleled plant material in Saline-Alkali stress research [ 3 , 4 , 5 ]. Lilium pumilum in this study grows naturally in the heavily salinized and alkalized meadow of Daqing suburb of the Songnen Plain with soil pH as high as 9–10.…”
Section: Introductionmentioning
confidence: 99%
“…The Lilium pumilum is an excellent plant material because of its high salt tolerance and suitability for alkaline soils. 1 , 2 We analyzed and compared the differential transcriptome of Lilium pumilum without treatment and under 20 mM NaHCO 3 treatment. The results indicated that the expression of the CPC gene was significantly increased under 20 mM NaHCO 3 treatment.…”
Section: Introductionmentioning
confidence: 99%